1998
DOI: 10.1161/01.cir.97.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Ischemia/Reperfusion Injury in Rats by a Caspase Inhibitor

Abstract: ZVAD-fmk was effective in reducing myocardial reperfusion injury, which could at least be partially attributed to the attenuation of cardiomyocyte apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
325
2
12

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(354 citation statements)
references
References 14 publications
15
325
2
12
Order By: Relevance
“…Previous studies have shown that application of caspase inhibitors prior to ischaemia confers protection against ischaemia-reperfusion injury in myocardium. For example, Z-VAD×fmk administered before, and continuously during and after an ischaemic insult resulted in better recovery and a smaller infarct size in rat heart in vivo (Yaoita et al, 1998). Holly et al (1999) have reported that caspase inhibition with the non-selective inhibitor Y-VAD×cmk prior to coronary artery occlusion in the rabbit heart in vivo led to limitation of infarct size.…”
mentioning
confidence: 99%
“…Previous studies have shown that application of caspase inhibitors prior to ischaemia confers protection against ischaemia-reperfusion injury in myocardium. For example, Z-VAD×fmk administered before, and continuously during and after an ischaemic insult resulted in better recovery and a smaller infarct size in rat heart in vivo (Yaoita et al, 1998). Holly et al (1999) have reported that caspase inhibition with the non-selective inhibitor Y-VAD×cmk prior to coronary artery occlusion in the rabbit heart in vivo led to limitation of infarct size.…”
mentioning
confidence: 99%
“…The Fas receptor (APO-1or CD-95) binds to FasL, Caspases can be inhibited by the apoptosis inhibitory protein (AIP), which can be displaced by the second activator of caspase-derived mitochondria (SMAC) [26]. Caspase inhibitors are being studied in an attempt to reduce the inflammatory response in models of cardiac ischemiareperfusion in rats [28]. In this sense, for example, preliminary results show that intravenous administration of Z-Val-Ala-DL-Asp-fluorometilquetone (ZVAD-fmk) has contributed at least partially, to the attenuation of apoptosis of cardiomyocytes [28].…”
Section: Apoptosismentioning
confidence: 99%
“…Caspase inhibitors are being studied in an attempt to reduce the inflammatory response in models of cardiac ischemiareperfusion in rats [28]. In this sense, for example, preliminary results show that intravenous administration of Z-Val-Ala-DL-Asp-fluorometilquetone (ZVAD-fmk) has contributed at least partially, to the attenuation of apoptosis of cardiomyocytes [28].…”
Section: Apoptosismentioning
confidence: 99%
“…Proof-of-principle experimental data in animal models indicate that caspase inhibition improves various conditions, including myocardial infarct (Table 1) or stroke-related ischemia/reperfusion injury of the brain, liver and other organs [35][36][37]. This protective effect is at least in part related to the limitation of the inflammatory response by caspase inhibition [38,39].…”
Section: Caspases: Modulators Of Apoptosis and Cytokine Maturationmentioning
confidence: 99%